O gênero Hypnea J.V. Lamouroux (Gigartinales, Rhodophyta) no Litoral do Estado da Bahia, Brasil: aspectos morfológicos e anatômicos - Jesus, Priscila Barreto de (2012)
There are currently reported in the literature 67 valid species of Hypnea (Guiry & Guiry 2012) which are widely distributed in tropical and subtropical seas. Wynne (2011) recognizes to the America's tropical and subtropical coast nine species of Hypnea: H. cenomyce J. Agardh, H. cervicornis J. Agardh, H. cornuta (Kützing) J. Agardh, H. krugiana Hauck, H. musciformis, H. nigrescens Grev. ex J. Agardh, H. spinella (C. Agardh) Kütz, H. valentiae (Turner) Mont. and H. volubilis Searles. Only H. krugiana was not cited for Brazil. Although some species of Hypnea are included in almost all Brazil's regional floras, detailed and updated taxonomic studies lack for most of them. There aren’t accurate analyses of the morphological and anatomical characters commonly used for the delimitation of these species resulting in numerous misidentifications in the Brazilian coast. The state of Bahia has the longest coastline among the states of Brazil, with 1.103 km long, and the occurrence of a representative number of species has been found there in relation to Brazilian and American coast. This number can be even greater as none of these studies had directed collections for this genus. Thus, considering the economic importance of the genus, the great extent of the coast of Bahia, the lack of specific literature and the current difficulty in identifying the species, a more detailed study of morphological and anatomical, vegetative and reproductive features used in taxonomy Hypnea is necessary. This work’s general aim is to develop taxonomic studies on species of Hypnea for the coast of Bahia, Brazil, based on morphological and anatomical characters. The specific aims are: to establish criteria for better taxonomic delimitation of species through the selection of consistent characteristics that contribute to the taxonomy of this genus; to understand the pattern of geographical distribution of species of Hypnea on the coast of Bahia, and to contribute to the knowledge of diversity of the marine benthic flora of the coast of Bahia, and consequently of the Brazilian coast. The genus Hypnea has a wide morphological variation among individuals of the same species, what can be influenced by environmental factors that occur in specific habitats. Furthermore, different circumscriptions have caused taxonomic confusion. Through the analysis of morphological and anatomical characters were recognized and illustrated eight species: H. cenomyce, H. cervicornis, H. cornuta, H. musciformis, H. nigrescens, H. Spinella, H. valentiae and Hypnea sp. For each species are given information and detailed taxonomic description, taxonomic comments and geographic distribution along the coast of Bahia and Brazil. A dichotomous key and a comparative table are also presented. Hypnea cornuta is reported for the first time to the coast of Bahia and this is the first valid citation of this species for northeastern Brazil. Hypnea platyclada Jesus et Nunes is described as a new species to science based on detailed morphological and anatomical observations. The morphological and anatomical characteristics that contributed to the delimitation of taxa were: type of apex; attachment to the substrate; type of insertion of the lateral branches on the axes; arrangement of the branches and branchlets in the axes; size and shape of periaxial cells, arrangement of tetrasporangia and spermatia in fertile branchlets. With this study, the coast of the state of Bahia becomes the most representative of Brazil in number of species of the genus Hypnea.